MENELAAH ASPEK YURIDIS PAJAK E-COMMERCE SEBAGAI LANGKAH EFEKTIF OPTIMALISASI PENERIMAAN NEGARA - Ega Ramadayanti; Tasya Safiranita Ramli; Zainal Muttaqin (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The trend of electronic transactions in Indonesia is getting more attention because it causes significant changes in all areas of life. The emergence of the Covid-19 Pandemic also changed the economic landscape towards a new economy, namely digital-based economic activities. However, the use of borderless internet saves the risks and challenges that are the potential for cybercrime. Not only that, other potential problems come from taxation that has not been able to optimize state revenue in terms of electronic commerce transactions (e-commerce). The dynamic proliferation of technology is not always followed by advancement in law. To respond to the problem's urgency, a literature review is carried out and learns the ideal system in other countries. The use of data is secondary data with three legal materials. Data is collected by literature studies conducted online and proceed by data analysis. The result showed the urgency to optimize state revenues from taxation to e-commerce tax collection for Value Added Tax, Income Tax, and Electronic Transaction using Permenkeu 48/PMK.03/2020 is also supported by optimization of Law No. 2/2020 with preventive, repressive, and adaptive measures to accommodate legal loopholes that are an obstacle to increasing state revenue